2013
DOI: 10.1002/jbm.a.34933
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium metal—A potential biomaterial with antibone cancer properties

Abstract: Reactive oxygen plays an important role in the pathogenesis of many serious illnesses, including bony cancer. Recently, it has been suggested that hydrogen (H2), a selective antioxidant, can effectively scavenge free radicals. Biomedical magnesium (Mg) used for bone defect repair in the surgery of bony cancer could release H2 because of the degradation, so Mg might have the potential to prevent bony cancer from metastasis and recurrence. In this study, alkali-heat treatment method was employed to modify the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…In addition, after AHT, Mg showed growth of calcium (Ca) phosphate-based apatite with a molar ratio of 1.858 after 14 days of immersion in SBF and no signs of morphological changes on cells or inhibitory effect on cell growth. The findings of Li et al (2004), Nan et al (2013) clearly show that AHT decreased the rate of degradation of Mg and its alloys in SBF, and the formation of an MgO layer is responsible for the observed improvement in resistance against corrosion. They soaked the MgeCa alloy in three different types of alkaline solutions, namely, Na 2 HPO 4 , Na 2 CO 3 , and NaHCO 3 for 24 h followed by heat treatment at 773 K for 12 h. During the initial alkaline treatment, depending on the type of alkaline solution, compounds such as magnesium carbonate, calcium carbonate, magnesium sodium phosphate, and calcium phosphate were deposited on the surface.…”
Section: Alkaline Heat Treatmentmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, after AHT, Mg showed growth of calcium (Ca) phosphate-based apatite with a molar ratio of 1.858 after 14 days of immersion in SBF and no signs of morphological changes on cells or inhibitory effect on cell growth. The findings of Li et al (2004), Nan et al (2013) clearly show that AHT decreased the rate of degradation of Mg and its alloys in SBF, and the formation of an MgO layer is responsible for the observed improvement in resistance against corrosion. They soaked the MgeCa alloy in three different types of alkaline solutions, namely, Na 2 HPO 4 , Na 2 CO 3 , and NaHCO 3 for 24 h followed by heat treatment at 773 K for 12 h. During the initial alkaline treatment, depending on the type of alkaline solution, compounds such as magnesium carbonate, calcium carbonate, magnesium sodium phosphate, and calcium phosphate were deposited on the surface.…”
Section: Alkaline Heat Treatmentmentioning
confidence: 86%
“…Pure Mg was soaked in supersaturated sodium bicarbonate (NaHCO 3 )emagnesium carbonate solution (starting pH of 9.3) for 24 h followed by heat treatment at 773 K for 10 h. After AHT, Mg showed an improved corrosion resistance in SBF, as evidenced by the lower loss of mass after 14 days of immersion and by a slow change in pH of the SBF observed during the first 6 days of immersion. Nan, Yangmei, and Bangcheng (2013) soaked commercially pure Mg (99.95% purity) in 5 mL of 1 M NaHCO 3 at 60 C for 24 h followed by heat treatment in air at 773 K for 10 h. According to them, the AHT reduced the rate of Mg degradation, supported by the slow change in the pH of SBF and smaller volume of hydrogen gas released during corrosion. studied the effect of AHT on the corrosion behavior of MgeCa alloy (1.4 wt% Ca).…”
Section: Alkaline Heat Treatmentmentioning
confidence: 99%
“…Because of the antioxidant properties of H 2 as stated above, Mg metal might possess a new function of anti‐oxidation by releasing H 2 . Our previous study proved preliminarily that Mg metal could decrease the level of ROS in cells and inhibit tumor growth . In this study, we used the oxidative stress damage model of mesenchymal stem cells (MSCs) to explore the response of antioxidant enzymes and mitochondria to Mg metal.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research studies evaluating the antitumor properties of Mg and its alloys have made significant progress . For instance, Mg implants were found to degrade in a certain period of time, so as to expose the tumor cells hidden in the implants, which in turn resulted in tumor cell death, a mechanism that could greatly prevent recurrence .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mg implants were found to degrade in a certain period of time, so as to expose the tumor cells hidden in the implants, which in turn resulted in tumor cell death, a mechanism that could greatly prevent recurrence . Degradation could also result in hydrogen (H 2 ) release, which could scavenge excess free radicals and resist tumor growth . It was also found that Mg–Ca–Sr–Zn alloy extracts could suppress the migration and invasion of tumor cells in vitro .…”
Section: Introductionmentioning
confidence: 99%